Shared Service Centres as a Management Tool in Government Administration in Poland: Reasons for Their Creation and Factors Determining the Process of Organisational Changes - Stąsiek, Iwona (Journal of Public Governance, 2023)
Objective: The aim of the article is to present shared service centres diagnosed in government administration in Poland, their forms, models, objective, and subjective scope, the main problems and barriers in their creation, as well as factors determining the success in implementing this idea of public administration into practice. The main issues analysed are the motives for establishing SSCs in public administration, the problems occurring during implementation as well as the factors determining the success of the implementation of organisational changes in public administration. The basic research question is about the benefits of implementing shared service centres in public administration.Research Design & Methods: In the course of the research process, various methods were used, including the review and analysis of the literature as well as an analysis of legal acts and regulations of identified SSCs in government administration in Poland. Apart from desk research method, the empirical research in the quantitative approach (survey study) was used.Findings: This research indicates that SSCs are an example of a tool supporting the management of organisations, which brings measurable benefits such as better use of resources, standardisation, higher quality of service, and cost savings due to economies of scale. Due to these advantages and despite no formal regulation the idea of SSC is used in government administration in Poland. There is no single model of SSCs in central government administration in Poland. A common feature of SSCs established in government administration in Poland is their evolutionary and voluntary character. The scope of services entrusted to the separated entities concerned mainly logistics activities as well as IT management and IT support.Implications / Recommendations: Taking into account the specificity of government administration, there is a potential to use this tool at the voivodeship level. At the same time, it should be emphasised that the complexity of the process determines the proper planning of the change process, considering the key determinants of success, i.e. formal, legal, and organisational conditions, including, above all, the human factor. Change management skills, management determination and support, as well as communication are all very important success factors.Contribution / Value Added: This article contributes to understanding the idea and the complexity of the SSC implementation process in public administration.Article classification: research articleJEL classification: H11